2013
DOI: 10.1111/and.12121
|View full text |Cite
|
Sign up to set email alerts
|

Intratesticular action of kisspeptin in rhesus monkey (Macaca mulatta)

Abstract: Kisspeptin-Kiss1R signalling in mammals has been implicated as an integral part of the reproductive cascade. Kisspeptinergic neurons upstream of GnRH neurons are involved in the activation of the hypothalamic GnRH pulse generator during pubertal onset. Thus, the major research focus has been on the central effects of kisspeptin. The demonstration of the presence of KissR expression in human testes suggests additional unknown actions of kisspeptin-KISS1R signalling at the distal component of the male reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 28 publications
0
25
1
Order By: Relevance
“…The pituitary, which is vital in the control of metabolic homeostasis and reproduction, highly expresses Rfrp, GnIHR, Kiss1, and Kiss1r (Lee et al 1996, Muir et al 2001, Ohtaki et al 2001, Shahab et al 2005, Ubuka et al 2009b, Smith et al 2010a,b, Tsutsui et al 2010, Wahab et al 2011a, Cejudo Roman et al 2012, Irfan et al 2014.…”
Section: Kp and Gnih Signaling In Conditions Of Altered Energy Balancmentioning
confidence: 99%
See 1 more Smart Citation
“…The pituitary, which is vital in the control of metabolic homeostasis and reproduction, highly expresses Rfrp, GnIHR, Kiss1, and Kiss1r (Lee et al 1996, Muir et al 2001, Ohtaki et al 2001, Shahab et al 2005, Ubuka et al 2009b, Smith et al 2010a,b, Tsutsui et al 2010, Wahab et al 2011a, Cejudo Roman et al 2012, Irfan et al 2014.…”
Section: Kp and Gnih Signaling In Conditions Of Altered Energy Balancmentioning
confidence: 99%
“…These organs are crucial for the maintenance of metabolic homeostasis. Likewise, these genes are also expressed in the primary sex organs, ovaries, and testes, which drive reproduction (Ohtaki et al 2001, Li et al 2012, Irfan et al 2014. While the roles of GnIH-GnIHR and KP-Kiss1r in the functioning of these peripheral organs are not fully understood at present, the modulation of these organs' endocrine secretion by the administration of GnIH and KP suggests a significance of GnIH and KP expression in the periphery.…”
Section: Kp and Gnih Signaling In Conditions Of Altered Energy Balancmentioning
confidence: 99%
“…However, this reduction was not a complete inhibition of testosterone release, which suggested that the P234 did not have a robust effect. Although there have been preliminary reports of the presence of GPR54 in the monkey testis (Irfan et al, 2008;Tariq et al, 2010), initial findings from our laboratory have . a) Time course of plasma testosterone levels (mean ± SEM) before and after vehicle or P234 intravenous bolus injection (38.8 µg/kg BW; arrow) in adult male rhesus monkeys (n = 5).…”
Section: Discussionmentioning
confidence: 68%
“…Hence, one could speculate that this might indicate a dose-related direct effect of kisspeptin-54 at the testes. Kisspeptin-54 receptors are present in the testes, and kisspeptin-54 has been observed to significantly increase hCG-stimulated testosterone response in monkeys, consistent with a direct testicular action [37]. …”
Section: Discussionmentioning
confidence: 99%